Sphingomyelinase Activity ofTrichomonas vaginalisExtract and Subfractions - González Salazar, Francisco; Garza González, Jesús Norberto; Hernández Luna, Carlos Eduardo; Mata Cárdenas, Benito David; Carranza Rosales, Pilar; Castro Garza, Jorge Enrique; Hernández García, Magda Elizabeth; Vargas Villarreal, Javier (2013)
Trichomoniasis is one of the most common acute sexually transmitted curable diseases, and it is disseminated worldwide generating more than 170 million cases annually. Trichomonas vaginalis is the parasite that causes trichomoniasis and has the ability to destroy cell monolayers of the vaginal mucosa in vitro. Sphingomyelinases (SMase) are enzymes that catalyze the hydrolysis of sphingomyelin into ceramide and phosphorylcholine. Ceramide appears to be a second messenger lipid in programmed apoptosis, cell differentiation, and cell proliferation. Sphingomyelinase is probably a major source of ceramide in cells. Signal transduction mediated by ceramide leads cells to produce cytokine induced apoptosis during several inflammatory responses. SMase are also relevant toxins in several microorganisms. The main objective of this research is to identify SMase activity of T. vaginalis in the total extract (TE), P30, and S30 subfractions from brooked trophozoites. It was found that these fractions of T. vaginalis have SMase activity, which comes principally from P30 subfraction and was mainly type C. Enzymatic activity of SMase increased linearly with time and is pH dependent with two peaks by pH 5.5 and pH 7.5. The addition of manganese to the reaction mixture increased the SMase activity by